2021
DOI: 10.3389/fmolb.2020.598599
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Immunocorrelation of Prognosis-Related Genes Associated With Development of Muscle-Invasive Bladder Cancer

Abstract: Improved understanding of the molecular mechanisms and immunoregulation of muscle-invasive bladder cancer (MIBC) is essential to predict prognosis and develop new targets for therapies. In this study, we used the cancer genome atlas (TCGA) MIBC and GSE13507 datasets to explore the differential co-expression genes in MIBC comparing with adjacent non-carcinoma tissues. We firstly screened 106 signature genes by Weighted Gene Co-expression Network Analysis (WGCNA) and further identified 15 prognosis-related genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The correlation was higher in paracancerous tissues, indicating that the interaction between ANLN and ASPM also exists in normal tissues. Previous studies have confirmed ANLN and ASPM as risk factors for the prognosis of patients with BLCA through silico data analysis (Chen et al, 2019;Wang et al, 2019;Xu et al, 2019;Li et al, 2020;Liu et al, 2021b). Our study aimed to further discuss the impact of these genes on BLCA.…”
Section: Association Of Anln and Aspm With The Clinicopathological Fe...mentioning
confidence: 80%
“…The correlation was higher in paracancerous tissues, indicating that the interaction between ANLN and ASPM also exists in normal tissues. Previous studies have confirmed ANLN and ASPM as risk factors for the prognosis of patients with BLCA through silico data analysis (Chen et al, 2019;Wang et al, 2019;Xu et al, 2019;Li et al, 2020;Liu et al, 2021b). Our study aimed to further discuss the impact of these genes on BLCA.…”
Section: Association Of Anln and Aspm With The Clinicopathological Fe...mentioning
confidence: 80%
“…Then, the single-sample gene set enrichment (ssGSEA) method in GSVA R-package was carried out to quantitate the infiltration levels of these gene sets. The ssGSEA score of individual immune cell types was standardized by the equation of our previous study (17). The proportion of 22 immune cell types for an individual sample was computed by Cell Type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT).…”
Section: Analysis Of Immune Infiltration and Metabolic Reprogrammingmentioning
confidence: 99%